Common Memory, Differences in Memory: Post-War Historical Memory since 1945 in Contemporary Polish and Romanian School History Textbooks - Kererush, Volha (Sensus Historiae, 2025)
In this article, I address the issue of historical memory of the post-war period until 1989 in school history textbooks in Poland and Romania. In order to obtain a more detailed picture of the context in which the analyzed textbooks are situated, I examined the educational systems and history curriculum in both countries, which I also described in the article. Above all, however, I subjected the textual and visual layers of the analyzed textbooks to a quantitative and qualitative analysis and, on this basis, I conducted a comparative analysis of selected elements of the school textbook narrative, including historical figures, which is particularly the subject of my text.